How Does AI Enable Health Risk Assessment? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
In the ever-evolving landscape of healthcare, the pursuit of precision and proactivity in patient care has led to the adoption of groundbreaking technologies...
Keywords: AI in Public Health; Enable; Health; Assessment; Artificial Intelligence; Healthcare; Patient Care